Asian summer monsoon anticyclone: trends and variability - G. Basha; M. V. Ratnam; P. Kishore (Atmospheric Chemistry and Physics, 2020)
The Asian summer monsoon anticyclone (ASMA) has been a topic of intensive research in recent times regarding its variability in dynamics, chemistry and radiation. This work explores the spatial variability and the trends of the ASMA using observational and reanalysis data sets. Our analysis indicates that the spatial extent and magnitude of the ASMA is greater during July and August than in June and September. The decadal variability of the anticyclone is very large at the edges of the anticyclone compared with the core region. Significant decadal variability is observed in the northeastern and southwestern parts of the ASMA with reference to the 1951–1960 period. The strength of the ASMA shows a drastic increase in zonal wind anomalies in terms of temporal variation. Furthermore, our results show that the extent of the anticyclone is greater during the active phase of the monsoon, strong monsoon years, and La Niña events. Significant warming with strong westerlies is observed exactly over the Tibetan Plateau from the surface to the tropopause during the abovementioned periods. Our results support the existence of transport process over the Tibetan Plateau and the Indian region during active, strong monsoon years and during strong La Niña years. Therefore, it is recommended that the different phases of the monsoon be taken into account when interpreting the variability of pollutants and trace gases in the anticyclone.